The antioxidant system of sterlet seminal fluid in testes and Wolffian ducts - Dzyuba, Viktoriya; Dzyuba, Borys; Cosson, Jacky; Boryshpolets, Sergii; Yamaner, Gunes; Kholodniy, Vitaliy; Rodina, Marek (Fish physiology and biochemistry, 2014)
Oxidative stress is a possible source of spermatozoa function deterioration. Seminal fluid (SF) protects spermatozoa against reactive oxygen species (ROS) attack during development in testes and transit through the reproductive tract. Spermatozoa curvilinear velocity and percent of motile cells as well as changes in thiobarbituric acid-reactive substance (TBARS) content, superoxide dismutase, and catalase activity, and uric acid concentration in SF were evaluated in sterlet sperm collected from testes 24 h after hormone induction of spermiation and from Wolffian ducts at 12, 24, 36, and 60 h after hormone injection (HI). While testicular spermatozoa motility was not initiated in activating medium, Wolffian duct sperm showed low motility at 12 h, significant increase at 24 and 36 h, and decrease at 60 h. Testicular SF was characterized by the highest level of TBARS and activity of studied enzymes compared with SF from Wolffian duct sperm at 24 h post-HI. In fluid from Wolffian duct sperm, a significant increase in TBARS content was shown at 36-60 h post-HI. In contrast to testicular SF, in SF from Wolffian duct sperm, this increase was not counterbalanced by changes in the studied variables of antioxidant system. This may be the source of the observed decrease in spermatozoa motility parameters 60 h post-HI. The results may confirm a dual role of ROS in fish sperm physiology. The data with respect to decrease in sturgeon spermatozoa motility parameters at 60 h post-HI should be taken into account in artificial sturgeon propagation.
Keywords: Animals; látky reagující s kyselinou thiobarbiturovou; Uric Acid; kyselina močová; Semen; počet spermií; zvířata; ryby; Fishes; Male; Wolffovy vývody; spermie; antioxidancia; Thiobarbituric Acid Reactive Substances; Spermatozoa; Wolffian Ducts; sperma; Antioxidants; mužské pohlaví; Sperm Count